Characterization of Metabolic Alterations in Mouse Models of Neurodevelopmental Disorders - Menzies, Caitlin (Université d'Ottawa / University of Ottawa, 2021)
Background: Prevalence of metabolic disturbances is higher among individuals with neurodevelopmental disorders (NDDs), yet this association has been poorly studied. Investigation into human disease remains challenging, as a complete pathophysiological understanding relies on accurate modeling and highly controlled variables. As such, genetically engineered mouse models are increasingly used to gain insight into the biology of human NDDs, but preclinical research focus has been mainly on behavioral and neurophysiological abnormalities. Mouse models engineered to embody human-equivalent genetic variations can display discrepancies to human phenotypes, therefore a thorough characterization of mouse phenotypes must be conducted in order to evaluate how accurately a mouse model embodies a human phenotype. Also, mouse models can help discover unsuspected abnormalities that can be further validated in humans. Objective: In this study, we sought to investigate the metabolic alterations derived from NDD-associated genetic polymorphisms in previously-validated genetic mouse models. Due to the similarities in NDD-associated phenotypic expression, we hypothesized that our NDDs of interest would express similar metabolic signatures. Further, we anticipated that we might uncover unknown metabolic anomalies, and that sex may alter these differences. Methods: We used the Comprehensive Lab Animal Monitoring System coupled to EchoMRI, as well as quantification of key plasma metabolites by liquid chromatography-mass spectrometry to characterize and compare basal metabolism in three mouse models of NDDs, namely Down syndrome (Dp(16)Yey/+ mice), 16p11.2 deletion syndrome (16p11.2df/+ mice) and Fragile X syndrome (Fmr1-/- KO mice) and their wild-type (WT) counterparts. Results: Our study reveals that each mouse model expresses a unique metabolic signature that is sex-specific, independent of the amount of food consumed and minimally influenced by physical activity. We found striking differences in body composition, respiratory exchange ratio, caloric expenditure and concentrations of circulating plasma metabolites related to mitochondrial function. Conclusion: Providing novel insight into NDD-associated metabolic alterations provides a basis for future studies aimed at understanding physiological mechanisms and provides a point of reference for research aimed at detecting changes in response to intervention.
Keywords: Neurodevelopmental disorders; Metabolism; Metabolites; Autism; 16p11.2 Deletion Syndrome; Fragile X Syndrome; Down Syndrome